Outbreak of Measles Amongst USA-Bound Afghan Evacuees - Elise Buisson (University of New South Wales, 2021)
This Watching Brief describes an outbreak of measles in the context of the mass evacuation of 124,000 people from Afghanistan to the USA. Cases were identified in the States of Wisconsin and Virginia, as well as in a military base in Germany. The outbreak affected children and young people aged 0 - 26 years, with publicly available data indicating a roughly even gender divide. As in previous measles outbreaks amongst displaced populations, a mass vaccination campaign played a foundational role in curbing the described outbreak.